Wheelchair use in ultra-lightweight wheelchair users. - Sonenblum, Sharon Eve; Sprigle, Stephen (Disability & Rehabilitation: Assistive Technology, 2017)
Purpose:The goal of this study was to describe how ultra-lightweight wheelchair users use their wheelchairs during everyday mobility. Method:We instrumented a convenience sample of 69 ultra-lightweight wheelchair users with a seat switch to measure their occupancy, and an accelerometer on their wheel to measure distance wheeled, time spent wheeling and daily bouts of mobility. Results:On the median day, subjects wheeled 83 bouts and 1.4 km over 45 min. A typical bout of mobility was 8.3 m in length, lasting 20 s and occurring at a speed of 0.44 m/s. Fast (>1 m/s) and long (>2 min) bouts represented less than 4% of bouts and were more common among younger participants and those who were employed or a student. Conclusions:Highly functional manual wheelchair users present with a significant mobility disability, moving far less than their ambulating peers despite moving with similar mobility characteristics. The typical bout characteristics – short and slow bouts – are consistent with indoor mobility and transitions between functional activities. For wheelchair users, it highlights the importance of manoeuverability and the need for prescription and training to emphasize manoeuverability.Implications for RehabilitationMeasurement of wheelchair use, both how and how much, might provide unique insight to what equipment would be most appropriate for an individual.Participants who used an ultralight wheelchair presented with a significant mobility disability, wheeling only 1.7 km/day on average.Fast (>1 m/s) and long (>2 min) bouts are uncommon, representing less than 4% of bouts. Younger participants and those who were employed or a student were more likely to wheel one fast and long bout per day.Because wheelchair mobility was dominated by short, slow bouts, prescription and training need to emphasize maneuverability.